1991
DOI: 10.1007/bf00047045
|View full text |Cite
|
Sign up to set email alerts
|

First-order invariants of Euclidean motions

Abstract: Let E(n) be the Lie group of proper rigid motions of Euclidean n-space. The paper is concerned with the adjoint action of E(n) on its Lie algebra e(n), and the induced action on the Grassmannian of subspaces of e(n) of a given dimension. For the adjoint action, the authors list explicit generators for the ring of invariant polynomials. In the case n = 3, of greatest physical interest, explicit finite invariant stratifications are given for the Grassmannians, providing a formal listing of the screw-systems fami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

1993
1993
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 8 publications
(8 reference statements)
0
16
0
Order By: Relevance
“…However, the equivalence relation underlying the listing was not explicit, raising doubts about its completeness. This situation was rectified in [27], and a classification was described intrinsically by the present authors in [14] following the original philosophy of Klein. In [15] we showed that the listing gave rise to natural Whitney stratifications, and gave complete descriptions of the specialisations.…”
Section: Screw Systemsmentioning
confidence: 94%
See 1 more Smart Citation
“…However, the equivalence relation underlying the listing was not explicit, raising doubts about its completeness. This situation was rectified in [27], and a classification was described intrinsically by the present authors in [14] following the original philosophy of Klein. In [15] we showed that the listing gave rise to natural Whitney stratifications, and gave complete descriptions of the specialisations.…”
Section: Screw Systemsmentioning
confidence: 94%
“…The group SE(p) behaves like a geometrically reductive group, in that the ring of invariant polynomials for the adjoint action is finitely generated. In [14] we gave explicit generators, the form depending on the parity of p. When p = 3 the ring is generated by the Klein and Killing forms, a result implicit in the subject but for which we are not aware of any prior reference.…”
Section: Screw Systemsmentioning
confidence: 99%
“…It inherits from the group structure described in Section 1 the structure of a semi-direct product of the Lie algebras so(3) of the rotation group and t(3) of the translation group. Thus, elements may be represented by a pair (B, v) ∈ so (3) Following ideas in [21,22], the following local equivalence was defined in [23], where it is assumed that coordinates are chosen so that at the configuration x ∈ M , λ(x) = 1 (the group identity). Definition 6.1.…”
Section: Screw Systemsmentioning
confidence: 99%
“…In particular its Killing form is degenerate and the polynomial invariant theory for reductive algebras does not apply. Donelan and Gibson [23] determined generators for the ring of invariant polynomials for the adjoint action of SE(n) and in particular:…”
Section: Screw Systemsmentioning
confidence: 99%
See 1 more Smart Citation